Annotated record of the detailed examination of Mn deposits from DSDP Site 70, Leg 8 (Cores 8-70-5, 8-70-7, 8-70A-9) - J I Tracey; George H Sutton; Wladimir D Nesteroff; J S Galehouse; Christopher C von der Borch; T Moore; J Lipps; Bilal U Haq; Jean-Pierre Beckmann (PANGAEA, 1971)
Site 70 is located about 20 miles north of the northern boundary of the Clipperton Fracture Zone near 140° W. It is the northernmost of the N-S line of sites drilled during Leg 8 to investigate the east-west trending accumulation of sediment centered at about 2°N near 140°W. It lies about 500 miles south of Site 42 of Leg 5, the southernmost of a line of sites continuing to the north. The R/V Argo SCAN survey indicated that the area was one of low, broad abyssal hills, 2 to 10 miles in width on E-W profiles, with relatively thick sediment cover.
Supplement to: Tracey, JI et al. (1971): Site 70. In: Tracey, J.I.Jr.; et al., Initial Reports of the Deep Sea Drilling Project, 8, Initial Reports of the Deep Sea Drilling Project, U.S. Government Printing Office, VIII, 135-284, https://doi.org/10.2973/dsdp.proc.8.105.1971